Pengaruh DAU dan DAK Terhadap Pertumbuhan Ekonomi Kota Banjarmasin - Ahaddin, Muhammad Fajrul; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The Influence of General Allocation Funds and Special Allocation Funds toEconomic Growth in Banjarmasin City. Economic growth or economic growth is theaggregate increase in national income or increase in output within a specific time.The population in this study is the Government of Banjarmasin City of SouthKalimantan Province. Hypothesis testing in this study using multiple linear regression.They have been collected from data analyzed first with a classical assumption test thentested by the SPSS 20 test instrument.The results showed that the General Allocation Fund had a positive effect oneconomic growth. It was evident from the results of the t-test obtained a significant valueof 0.028 <α where (α = 0.05) and Special Allocation Funds the t-test results were 0.002<α where (α = 0.05). The most dominant variable influencing economic growth inBanjarmasin City is the Special Allocation Fund because it has the smallest probability.Keyword: General Allocation Funds, Special Allocation Funds dan Economic Growth.